Peningkatan Kemampuan Literasi melalui Kegiatan “NOLITA” di Kelas 4 SDN Kemakmuran 2 - Hilda Hidansyah Agustin; Widia Nur Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy is a language skill used to communicate in various ways according to specific purposes. Literacy skills include listening, speaking, reading, writing, and critical thinking. It also involves the ability to understand, utilize, and respond to information from various sources. Literacy has become one of the main focuses of the national education curriculum. However, in reality, students in Indonesia still exhibit low reading interest. Therefore, literacy improvement activities are needed, one of which is the “NOLITA” program (watching, writing, and storytelling). NOLITA is a literacy enhancement program that incorporates three main activities: watching, writing, and storytelling. This program aims to improve the literacy skills of fourth- grade students by utilizing technological advancements to attract students’ interest and concentration, particularly through watching animated videos on a smart TV. After watching, students are asked to write a summary of the story and retell it at the end of the session. A supporting medium called the "Storytelling Picture Board" is used to help students remember the sequence of events in the story. This literacy activity was implemented at SDN Kemakmuran II, located at Jl. Pronggol No. 54, Lemahwungkuk District, Cirebon City, West Java. The results of the study show that through the NOLITA program, students’ basic literacy skills significantly improved, with an increase of 84.37%, categorized as high